Apego carencia afectiva. - Alcivar Reyes, Ana Gabriela (2018)
Within the research it has been observed that attachment and lack of affection is a problem that affects the emotional, physical and psychological development of children due to the lack of affection, affection, love and protection from their parents. That is why the objective is framed in determining the types of attachment and affective deficiency for the formation of the autonomy of children, this project, this project will work with the quantitative methodology directed with the techniques and instruments such as the interview, observation, survey among others. The main contributions of this project will be to know what is the secure, insecure and ambivalent attachment that will allow the development of children since it is not enough to just give them a good diet but also affection, that is, an emotional nutrition that goes hand in hand with the affectivity. Attachment, starts from the moment a child is born, occurs more frequently between the child and the mother because she is the one who is aware of what happens with her children. When there is a lack of affection in children, there are negative effects on their emotional and evolutionary development, producing difficulties in the future life of the children. The impact that this research work will have is to know if educational institutions take into account how the early emotional separation from their loved ones, especially their parents, influences the child and how this affects the development of children. The direct beneficiaries of this research will be the children, parents of the Centro Infantil del Buen Vivir "Santa Catalina".